2015
DOI: 10.1016/j.tcs.2015.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing polynomial time complexity of stream programs using interpretations

Abstract: This paper provides a criterion based on interpretation methods on term rewrite systems in order to characterize the polynomial time complexity of second order functionals. For that purpose it introduces a first order functional stream language that allows the programmer to implement second order functionals. This characterization is extended through the use of exp-poly interpretations as an attempt to capture the class of Basic Feasible Functionals (bff). Moreover, these results are adapted to provide a new c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…These only focus on soundness though. The paper [17] provides a characterization of polynomial time over the reals on first order programs using type-2 polynomial interpretations, which are however known to be untractable both at the level of inference and checking. In [18], it is shown that algebras and coalgebras may be encoded in the light affine lambda calculus while preserving polynomial time normalization properties.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These only focus on soundness though. The paper [17] provides a characterization of polynomial time over the reals on first order programs using type-2 polynomial interpretations, which are however known to be untractable both at the level of inference and checking. In [18], it is shown that algebras and coalgebras may be encoded in the light affine lambda calculus while preserving polynomial time normalization properties.…”
Section: Resultsmentioning
confidence: 99%
“…We have provided a first linear logic based characterization of polynomial time over the reals avoiding the use of untractable tools such as type-2 polynomials as in [17].…”
Section: Example: Average Of Two Real Numbersmentioning
confidence: 99%
“…Nevertheless, these characterizations are faced by at least two problems: (1) Characterizations using a general model of computation (whether machine-or programbased) require externally imposed and explicit resource bounding, either by a type-2 polynomial [KC91, KC96,FHHP15] or a bounding function within the class of [Con73,Meh76]. This is analogous to a shortcoming in Cobham's characterization of the class the light logic approach can deal with programs at higher types, its applications are restricted to type-1 complexity classes such as FP [BT04,BM10] or polynomial space [GMR08].…”
Section: Introductionmentioning
confidence: 99%
“…1. Characterizations using a general model of computation (whether machine-or program-based) require externally imposed and explicit resource bounding, either by a type-2 polynomial [Férée et al 2015;Cook 1991, 1996] or a bounding function within the class [Constable 1973;Mehlhorn 1976]. This is analogous to a shortcoming in Cobham's characterization of the class of (type 1) polynomial time computable functions FP [Cobham 1965].…”
Section: Introductionmentioning
confidence: 99%
“…Whereas the light logic approach can deal with programs at higher types, its applications are restricted to type-1 complexity classes such as FP [Baillot and Mazza 2010;Baillot and Terui 2004] or polynomial space [Gaboardi et al 2008]. Interpretations were extended to higher-order polynomials in [Baillot and Lago 2016] to study FP and adapted in [Férée et al 2015;Hainry and Péchoux 2017] to BFF 2 . However, by essence, all these characterizations use (at least) type-2 polynomials and cannot be considered as tractable.…”
Section: Introductionmentioning
confidence: 99%